Broadband and polarization-independent negative refractive index terahertz metamaterials. Issue 172 (12th June 2016) - Wang, Jian-min; Li, Xiao; Yao, Bo-wen
Abstract: In this paper, we proposed a broadband and polarization-independent negative refractive index (NRI) metamaterial structure for the terahertz range, which is composed of four heart-shaped split-ring resonators (HSRR) and two continuous wires printed on the two sides of a dielectric substrate respectively. The retrieved method and prism simulation demonstrate that the bandwidth of the negative refractive index response is 320 GHz for our structure. Owing to the symmetry of the structure, the proposed metamaterial can exhibit an isotropic NRI response for the perpendicularly polarized incident wave. Therefore, the proposed metamaterial is a good candidate material for designing the novel terahertz devices.